Reducing the buyer–seller information asymmetry in agricultural inputs markets in India - Sanjeev Kapoor; Niraj Kumar (Agricultural Economics Research Review, 2023)
Buyer–seller information asymmetry causes problems in economic exchanges between farmers and the agricultural inputs (agri-inputs) industry. This study examines farmers’ information needs regarding four important agri-inputs: seeds, fertilizers, agrochemicals, and farm machinery. The study reveals that while purchasing agri-inputs, farmers in India consider the experience and credence attributes like germination percentage, yield, packaging, impact on health, and soil condition critical to product quality and more important than price. The agri-inputs industry can reduce the buyer–seller information asymmetry while marketing their products, ensure their competitive advantage, and make farming more productive.